Dyadic approach to supervised community rehabilitation participation in an Asian setting post-stroke: exploring the role of caregiver and patient characteristics in a prospective cohort study - Hui Meng Chang; Chuen Seng Tan; Gerald Choon-Huat Koh; Narayanaswamy Venketasubramanian; David Bruce Matchar; Deidre Anne De Silva; Shilpa Tyagi; Nan Luo; Kelvin Bryan Tan; Helen Hoenig; Joanne Yoong; Angelique Chan; et al. (BMJ Open)
Objective To study the association of caregiver factors and stroke survivor factors with supervised community rehabilitation (SCR) participation over the first 3 months and subsequent 3 to 12 months post-stroke in an Asian setting.Design Prospective cohort study.Setting Community setting.Participants We recruited stroke survivors and their caregivers into our yearlong cohort. Caregiver and stroke survivor variables were collected over 3-monthly intervals. We performed logistic regression with the outcome variable being SCR participation post-stroke.Outcome measures SCR participation over the first 3 months and subsequent 3 to 12 months post-strokeResults 251 stroke survivor-caregiver dyads were available for the current analysis. The mean age of caregivers was 50.1 years, with the majority being female, married and co-residing with the stroke survivor. There were 61%, 28%, 4% and 7% of spousal, adult-child, sibling and other caregivers. The odds of SCR participation decreased by about 15% for every unit increase in caregiver-reported stroke survivor’s disruptive behaviour score (OR: 0.845; 95% CI: 0.769 to 0.929). For every 1-unit increase in the caregiver’s positive management strategy score, the odds of using SCR service increased by about 4% (OR: 1.039; 95% CI: 1.011 to 1.068).Conclusion We established that SCR participation is jointly determined by both caregiver and stroke survivor factors, with factors varying over the early and late post-stroke period. Our results support the adoption of a dyadic or more inclusive approach for studying the utilisation of community rehabilitation services, giving due consideration to both the stroke survivors and their caregivers. Adopting a stroke survivor-caregiver dyadic approach in practice settings should include promotion of positive care management strategies, comprehensive caregiving training including both physical and behavioural dimensions, active engagement of caregivers in rehabilitation journey and conducting regular caregiver needs assessments in the community.